A novel approach to monitoring selective fatigue in female softball athletes: evaluating load-velocity relationship variables and specific performance metrics - Zhang, Hongzhen; Li, Zhaoqian; Yu, Qiuyu; Cheng, Zan; Wang, Xiaoqing; Zhang, Xing; García-Ramos, Amador; Janicijevic, Danica (Frontiers in Physiology, 2026)
IntroductionThe purpose of this study was to assess whether bench press load-velocity (L-V) relationship variables serving as indicators of maximal theoretical force capacity (L0), maximal theoretical velocity capacity (v0), and maximal theoretical power capacity (Aline), as well as the softball-specific performance metrics (hit and throw distance), could be used to effectively monitor the selective fatigue induced by two different bench press training protocols.MethodsThe bench press L-V relationship variables and softball-specific performance metrics of 12 professional female softball players were measured on three separate occasions: (I) following passive rest (non-fatigue condition), (II) after light-load ballistic bench press throw (LLB), and (III) after heavy-load traditional bench press (HLT). Additionally, blood lactate and rating of perceived exertion (RPE) were assessed after LLB and HLT training protocols.ResultsA significantly lower v0, Aline and hit distance were found after both training protocols (p ≤ 0.008), with the LLB protocol revealing a higher fatigue compared with the HLT protocol. However, the change of L-V relationship variables and softball-specific performance metrics (0.15 ≤ ES ≤ 1.05) were not as sensitive as that of blood lactate and RPE (1.30 ≤ ES ≤ 1.78).DiscussionHence, changes in mechanical performance could be applied as a supplementary monitoring tool to be integrated into athletes’ daily routines, but should not be considered replacements for traditional fatigue indicators.